Social Work Education For Aboriginal Communities - Brown, Leslie A. (Canadian Journal of Higher Education, 1992)
This paper examines aboriginal social work education in Canada and suggests that current education practice may be facilitating the assimilation of aboriginal students into a mainstream culture and profession. Developments in aboriginal social work programs and curriculum are reviewed and a philosophy of recognition and accommodation of aboriginal perspectives as a basis for future developments is posed as an alternative to assimilation. Further, a strategy for teaching, termed interface teaching, is suggested as a way in which non-aboriginal educators can take individual responsibility for wrestling with some of the issues that arise in the professional education of aboriginal students.